ANALISIS PENGGUNAAN MEDIA DIGITAL DALAM PEMBELAJARAN ANAK USIA DINI DI TK EL SHADDAI - Parisu, Konstantia; Marmawi, Marmawi; Lukmanulhakim, Lukmanulhakim (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to describe the use of digital media in early childhood learning at El Shaddai Kindergarten, Pontianak City. The research method used is a descriptive method with a qualitative research form. The subjects in this research were 3 teachers who taught at El Shaddai Kindergarten, Pontianak City. The data collection techniques used were observation, interviews and documentation. The research results show that preparation for using digital media in early childhood learning is by preparing digital media that will be used during the learning process. Teachers choose and use forms of digital media that are appropriate to the child's age level and learning needs. Based on research results, the form of digital media used by teachers in learning influences the teaching and learning process, however, to use digital media well and correctly, the teacher must make an effort to guide and model it for children so that children can easily understand and apply it directly.